2000
DOI: 10.1002/(sici)1097-0320(20000601)40:2<109::aid-cyto4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Extension of osmolality-induced podia is observed from fluorescently labeled hematopoietic cell lines in hyperosmotic medium

Abstract: Background Since the description of long podia extended by hematopoietic cells and cell lines, the reliable elicitation of podia extensions is needed to study these podia systemically. In this study, hyperosmotic stress was considered as an elicitor. Methods Using two fluorescent membrane dyes PKH2 and PKH26, and an automated fluorescence microscopy system, morphological changes of seven human cell lines (six hematopoietic, one fibrosarcoma) at different osmolalities were monitored. Presence of surface molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…That study did not observe highly purified stem cells, however, the pseudopodia described therein bear some similarities to the proteopodia we report here. In fact, the same group recently reported that podia are induced by increased osmolality (Oh et al, 2000), as are the proteopodia we report here. A variety of actin-based cell surface membrane projections have been described on different cells, including microvilli, pseudopodia, lamellipodia, microspikes and filopodia (Cooper, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…That study did not observe highly purified stem cells, however, the pseudopodia described therein bear some similarities to the proteopodia we report here. In fact, the same group recently reported that podia are induced by increased osmolality (Oh et al, 2000), as are the proteopodia we report here. A variety of actin-based cell surface membrane projections have been described on different cells, including microvilli, pseudopodia, lamellipodia, microspikes and filopodia (Cooper, 1997).…”
Section: Discussionsupporting
confidence: 82%